Periodic version of the minimax distance criterion for Monte Carlo integration. (November 2020) - Eliáš, Jan; Vořechovský, Miroslav; Sadílek, Václav
Highlights: numerical integration with designs optimized via miniMax (mM) criterion is developed. mM designs with standard metric are nonuniform which may cause biased integration. the proposed periodic metric ensures point uniformity and unbiased robust integration. efficient construction algorithm for mM designs (standard or periodic) is developed. Abstract: The selection of points for numerical integration of the Monte Carlo type, largely used in analysis of engineering problems, is developed. It is achieved by modification of the metric in the minimax optimality criterion. The standard minimax criterion ensures the design exhibits good space-filling property and therefore reduces the variance of the estimator of the integral. We, however, show that the points are not selected with the same probability over the space of sampling probabilities: some regions are over- or under-sampled when designs are generated repetitively. This violation of statistical uniformity may lead to systematically biased integral estimators. We propose that periodic metric be considered for calculation of the minimax distance. Such periodic minimax criterion provides statistically uniform designs leading to unbiased integration results and also low estimator variance due to retained space-filling property. These conclusions are demonstrated by examples integrating analytical functions. The designs are constructed by two different algorithms: (i) a new time-stepping algorithm resembling a damped system of attracted particles developed here, and (ii) the heuristic swapping of coordinates. The designs constructed by the time-stepping algorithm are attached to the paper as a supplementary material. The computer code for construction of the designs is attached too.